Grönland im Strukturwandel von Wirtschaft und Siedlung, aufgezeigt am Beispiel des Raumes um Julianehåb - Dege, Wilhelm (ERDKUNDE, 1964)
Since about 1920 Greenland has experienced a rise in both sea and atmospheric temperatures. In the ice free area of Western Greenland the rise of the mean yearly air temperature has amounted to as much as 6° C. This, however, has almost exclusively made itself felt in less severe winters only. The water temperatures off the coast of western Greenland have risen maximally by 1.3° C compared with the mean average of previous decades. This climatic improvement seems to have come to a halt in 1950. This improvement has had far reaching consequences for the economy and settlement of the people, which are demonstrated in this paper by the example of the area around Julianehåb in the sub-arctic southwesternmost Greenland. Even in this area the original Eskimo hunting-fishing civilization permitted a largely subsistence economy as late as the beginning of this century. (Phoca hispida Schreb., Phoca groenlandia Fahr., Cystophora cristata Erxl.) Three seal species were the main prop of the economy. Sealing went hand in hand with pronounced features of seminomadism, viz. permanent winter quarters and temporary camping places at the respective sealing grounds. However, unlike in the arctic western Greenland it would have been wrong to speak of a nearly self-contained sealing civilization since for more than a century the catch of fjord cod, bass and halibut has formed an important part of the food supply. Fishing for export carried out from fishing stations founded for this purpose began here as early as 1910-11. Parallel with the climatic improvement went a catastrophic decline of the seal catch. However, as early as 1917 the marketable cod migrated into the coastal waters in such large numbers that transformation from a near subsistence to a world market economy was possible. The change-over was a difficult one since it involved the alteration of the most fundamental bases of the former civilization. True the area that supports the new economy remained the same as before but economic attitudes, catching gear, dietary habits and settlement had to change. The result has been the transformation of a sealing region into a fishing region - fishing being carried out all year round - with solidly built permanent settlements and a network of fishing stations. In these only the basic processing of the catch to salt or dried fish is carried out while in the fish factory at Narssaq processing includes quick freezing of cod fillets. Most fisher men operate in a small way with rowing boats, fishing by hooks and lines. However, the number of larger under takings which operate modern cutters and up to date gear is increasing steadily. Even this is coastal and fjord fishing only. To carry out fishing on the farther coastal shelf neither cutter sizes nor nautical training are yet sufficient. Fishing can be carried out very economically since in 1946 a deep water shrimp species was discovered in the fjords. Results are best in winter, thus filling the seasonal low in cod fishing. These shrimps are canned at Narssaq. The area of Julianehåb is also the centre of a flourishing sheep farming economy with about 27,000 of Greenland's total of 30,000 ewes. Sheep farming takes place in particular on the föhn belt in front of the ice sheet. In most years the föhn facilitates pasturing throughout the winter, without stalls or supplementary fodder. The facilities for pasturing are many and varied. The problem of the sheep farming is the provision of sufficient improved land for grain, silage and hay, which can only be succesfully cultivated in particularly favourable spots. Because of the greatly varying conditions of relief, local climate, soil and natural vegetation they are widely dispersed. Thus isolated farmsteads predominate. In almost every instance they are found on the same sites as the Viking farms of the 10th-15th centuries. The two largest Viking settlements, Eric the Red's estate Brattaklid and the bishop's see Gardar were able to grow to sheep farming villages. The tuns of the former Viking farms are today the nuclei of the improved land of Greenland's sheep farmers. Outfields, another element of this sheep farming landscape, originated independently. Connected with sheep farming is gardening, mainly growing of potatoes and May roots. On the coast many fishermen have also a few sheep as a side line. The purpose of the sheep farming is production of lambs for slaughter. This and the processing of the carcasses is carried out at the large abbatoir at Narssaq which has a capacity of 20,000 lambs per season (i. e. mid-August to mid-October). Nevertheless sealing has not disappeared altogether. There are now, however, only a few professional seal catchers, gene rally it is supplementary to fishing. The areas for sealing are the same as before, the catch depends on the amount of pack ice in a given year. Just as the central areas of sheep farming near the inland ice represent the interior boundary of the economic area, so are the sealing areas its boundary seawards. The concentration of the population at a few large centres of the fishing region applies here as it does in Green land as a whole. The former colonies of the colonial period, which have largely service and administrative functions, developed according to structure and function into modern small towns; the outposts of these became villages. The old dwelling sites, the typical small dispersed settlements of the sealing population, became increasingly abandoned. Instead many new settlements are coming into being in the sheep farming area.